Mediation of triple-negative breast cancer cell fate via cellular redox and Wnt signalling - Pohl, Sebastian Öther-Gee (Curtin University, 2018)
Breast cancer is the most common cause of malignancy affecting women worldwide. This thesis focusses on the role of DDX20 in regulating Wnt/β-catenin signalling and its impact on cell fate in triple-negative breast cancer (TNBC). The results of this study demonstrated a new role for DDX20-mediated Wnt signalling governing intracellular redox and mitochondrial function. Furthermore, we have determined that DDX20 is an essential regulator of Wnt/β-catenin signalling in TNBC stem cells.